Bimodal Therapeutic Agents Against Glioblastoma, One of the Most Lethal Forms of Cancer. Issue 63 (6th October 2020) - Couto, Marcos; Alamón, Catalina; Nievas, Susana; Perona, Marina; Dagrosa, María Alejandra; Teixidor, Francesc; Cabral, Pablo; Viñas, Clara; Cerecetto, Hugo
Abstract: About 95 % of people diagnosed with glioblastoma die within five years. Glioblastoma is the most aggressive central nervous system tumour. It is necessary to make progress in the glioblastoma treatment so that advanced chemotherapy drugs or radiation therapy or, ideally, two‐in‐one hybrid systems should be implemented. Tyrosine kinase receptors–inhibitors and boron neutron capture therapy (BNCT), together, could provide a therapeutic strategy. In this work, sunitinib decorated‐carborane hybrids were prepared and biologically evaluated identifying excellent antitumoral‐ and BNCT‐agents. One of the selected hybrids was studied against glioma‐cells and found to be 4 times more cytotoxic than sunitinib and 1.7 times more effective than 10 B‐boronophenylalanine fructose complex when the cells were irradiated with neutrons. Abstract : Compounds for bimodal cancer‐treatment, based on tyrosine kinase receptors–inhibitors and boron neutron capture therapy (BNCT), were successfully developed. The single molecules, sunitinib decorated‐carborane hybrids, could represent a significant advance in cancer treatment (see figure).